BUILDING INTERFAITH HARMONY: AN ANALYSIS OF THE MEDIA AND THE VALUE OF NA TOLU'S EXCUSE IN MUSLIM-CHRISTIAN RELATIONS - Godlif Sianipar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2022)
This study analyzes the role of the media and local cultural values of Dalihan Na Tolu in building interfaith harmony between the Muslim and Christian communities in Tapanuli, North Sumatra. Through media content analysis methods, in-depth interviews, participant observations, and documentation, this study found that local media highlighted more interfaith cooperation and dialogue, which contributed positively to harmonious relations between communities. Dalihan Na Tolu values, such as somba marhula-hula (respect for elders) and elek marboru (helping each other), are applied consistently in social interactions, including in interfaith contexts. Community leaders and religious leaders play an important role in maintaining these values, while the challenges of social media that can trigger tensions are successfully managed through the strengthening of local cultural values. The conclusion of this study confirms that the synergy between responsible media, the application of cultural values, and effective leadership is very important in maintaining and strengthening interfaith harmony. This research provides valuable insights into how interfaith harmony can be maintained amid the challenges of modernization and globalization of information.